Comparative evaluation of the left ventricular mass in patients with chronic kidney disease in periodontally healthy, chronic gingivitis, and chronic periodontitis patients - Kolte, Rajashri A.; Kolte, Abhay P.; Shah, Kanan K.; Modak, Anil; Sarda, Trupti S.; Bodhare, Girish H. (International Journal of Health Sciences, 2019)
Objectives: Emerging evidence suggests that inflammation due to periodontal diseases may not be limited to adjacent oral tissues but may have influence on systemic diseases such as chronic kidney diseases (CKD) and cardiovascular diseases. Hence, this study was aimed to evaluate and compare left ventricular mass (LVM) in patients with CKD undergoing hemodialysis (CKDH) in periodontally healthy, chronic gingivitis, and chronic periodontitis. Methodology: A total of 60 patients diagnosed with CKDH were divided equally into three groups based on periodontal status as CKDH patients with healthy periodontium (Group I), CKDH patients with chronic gingivitis (Group II), and CKDH patients with chronic periodontitis (Group III). These patients were assessed clinically, biochemically, and echocardiographically. LVM in each of these patients was calculated according to Devereux formula and was indexed to height. Results: Group II and Group III patients exhibited higher mean LVM of 199.51 ± 40.17 g and 200.35 ± 65.04 g, respectively, as compared to Group I of 161.56 ± 27.99 g. Similarly, LVM index (LVMI) was found to be more in Group II and Group III at 59.36 ± 13.14 g/m2.7 and 57.83 ± 19.94 g/m2.7, respectively, while it was 45.99 ± 11.87 g/m2.7 for Group I patients. Conclusion: Increasing the severity of periodontal diseases in CKDH patients is associated with increase in LVM and LVMI. Periodontal screening and intervention would enable the clinician to refine cardiovascular risk assessment in such patients.